Effects of the atmosphere and substrate on the crystallization of PLZT thin films - Simões, A.z. [UNESP]; Gonzalez, A.h.m. [UNESP]; Zaghete, M.a. [UNESP]; Varela, J.a. [UNESP]; Stojanovic, B.d. (ABM, ABC, ABPol, 2000)
Lead lanthanum zirconate titanate [PLZT (9/65/35)] thin films were prepared by dip-coating on Si (100) or Si/Ti/Pt (100) substrates using a polymeric precursor solution and annealed at 650 °C for 3 h. Perovskite phase formation of the PLZT thin films and microstructure were analysed using XRD and SEM. Effects of Si (100), Si/Ti/Pt (100) substrates and atmosphere on crystallization of PLZT thin films were studied. Films deposited on platinum coated silicon (100) show a heterogeneous surface with presence of bubbles. Otherwise, the PLZT (9/65/35) thin films deposited on silicon (100) substrate shows a more uniform surface after annealing in oxygen atmosphere.
Keywords: PLZT; Pechini method; dip-coating; crystallization